Measurement of Communication Skills in the Learning Process: A Quantitative Descriptive Study - Isnandar; Pramana, Heri; Nurhadi, Didik (STAI Miftahul Ula Nganjuk, 2025)
Modernization and demands of the industrial world demand vocational school graduates have skills harmonious communication? with need Work 21st century . Research This aim For describe skills communication student Class X Casting Engineering Metal of State Vocational School 1 Grati Pasuruan in context learning . The background is demands of the world of work the 21st century which places communication as competence base , parallel with think critical , collaboration , and creativity ( 4C ), which are essential for teacher professionalism and readiness Work students . Communication Alone understood covers verbal and nonverbal aspects . Research This use approach quantitative with type descriptive and involving population fed up as much as 57 students . Data collection was carried out use questionnaire 4- point Likert scale consisting of from 13 grains statements that measure five aspects communication skills 4. Instruments? study has tested and declared valid ( r range = 0.561 - 0.775) and has very high reliability (alpha = 0.912). The results of the analysis descriptive show that skills communication student in a way general is in the category Enough good . Indicator with score highest is value opinions and ideas from others (M=3.47), which reflects strength student in aspect attitude communication . On the other hand , indicators with score lowest is give relevant responses? in conversation / presentation (M=2.26), indicating that part big student Still passive in verbal expression . In addition , the aspect other performatives such as use Language body and adjustment style communication is still there need improved . Findings This indicates that student has own foundation attitude good communication ( polite? polite , respectful , controlling emotions ), but aspect courage speaking , verbal expression , and use Language body Still must developed . Implications study suggest teachers to multiply activity interaction - focused learning? active like role play , debate , or Project-Based Learning For increase trust students' self and verbal expression . (10pt)